A mixed methods exploration of secondary students' attitudes and intentions in relation to elective science course enrollment. (21st October 2021) - Summers, Ryan
Abstract: Many students have the opportunity to enroll in elective courses during secondary school and the choices they make about pursuing specific electives may foreshadow future outcomes. The present study utilized a sequential, mixed methods design to investigate the association between students' attitudes toward science, their declared intentions to engage with science in the future, and their eventual decision to enroll in an elective science course. Students in grades 9 through 11 completed a 30‐item survey rooted in the theories of reasoned action and planned behavior, which provided self‐report data about their attitudes, intentions, and related variables ( N  = 698). Course enrollment data were obtained during the following academic year for a sub‐sample of Grade 12 students who previously completed the survey. Pathway analysis supported the theoretical model and explained a majority of the variance between students' reported intentions and their actual course enrollment. Other factors that students considered when making their decisions were investigated through group interviews. Based on interviews conducted, students that enrolled in an elective science course generally saw science as a part of their post‐secondary plans.